2020
DOI: 10.1155/2020/8352579
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA NEAT1 Regulates TGF-β2-Induced Epithelial-Mesenchymal Transition of Lens Epithelial Cells through the miR-34a/Snail1 and miR-204/Zeb1 Pathways

Abstract: The aim of this study was to explore whether the long noncoding RNA nuclear paraspeckle assembly transcript 1 (NEAT1)/miR-34a/Snail1 and NEAT1/miR-204/Zeb1 pathways are involved in epithelial-mesenchymal transition (EMT) of lens epithelial cells (LECs). Primary human LECs (HLECs) were separated and cultured. Our results identified that TGF-β2 induces NEAT1 overexpression in a dose-dependent manner and a time-dependent manner. Additionally, TGF-β2 induced downregulation of E-cadherin and upregulation of fibrone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 42 publications
(98 reference statements)
0
3
0
Order By: Relevance
“…PCO mainly comes from the proliferation, migration, fibrosis, and EMT of LECs in the lens capsule after stimulation by several growth factors and cytokines [ 43 ]. The development of anterior subcapsular cataract (ASC) and PCO closely relates to the EMT of LECs triggered by a diverse set of stimuli, of which the TGF-β2 growth factor is one of the most [ 44 , 45 ]. Previous studies demonstrated that TGF-β2 played an essential role in the formation of PCO via the canonical TGF-β/Smad signaling pathway, as well as via non-canonical signaling [ 20 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…PCO mainly comes from the proliferation, migration, fibrosis, and EMT of LECs in the lens capsule after stimulation by several growth factors and cytokines [ 43 ]. The development of anterior subcapsular cataract (ASC) and PCO closely relates to the EMT of LECs triggered by a diverse set of stimuli, of which the TGF-β2 growth factor is one of the most [ 44 , 45 ]. Previous studies demonstrated that TGF-β2 played an essential role in the formation of PCO via the canonical TGF-β/Smad signaling pathway, as well as via non-canonical signaling [ 20 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Long non-coding RNAs (LncRNAs) can regulate a variety of biological functions in the body. Among the nuclear transcription factors, LncRNA NEAT1 has been reported to be involved in the invasion, migration and EMT of a variety of tumor cells, including osteosarcoma cells (Chen et al 2021), lens epithelial cells (Dong 2020), endometrioid adenocarcinoma cells (Li et al 2016) and retinoblastoma cells (Luan et al 2021). These studies demonstrate that NEAT1 promotes cancer progression, migration, invasion and EMT.…”
Section: Introductionmentioning
confidence: 99%
“…It plays a vital role in the activation and promotion of EMT in LECs through the Smads pathway, PI3K/Akt pathway, and other pathways. Besides, TGF-β2 is the primary subtype of the TGF-β family in aqueous humor (Dong, 2020;Zhang et al, 2017). Therefore, TGF-β2induced human lens epithelial cells (HLECs) can be used to simulate the PCO microenvironment (Wang et al, 2019;Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%